Artificial Life Models in Hardware - Adamatzky, Andrew; Komosinski, Maciej (Springer London : Imprint: Springer, 2009)
Hopping, climbing and swimming robots, nano-size neural networks, motorless walkers, slime mould and chemical brains --- this book offers unique designs and prototypes of life-like creatures in conventional hardware and hybrid bio-silicon systems. Ideas and implementations of living phenomena in non-living substrates cast a colourful picture of state-of-the-art advances in hardware models of artificial life. Focusing on topics and areas based on non-traditional thinking, and new and emerging paradigms in bio-inspired robotics, this book has a unifying theme: the design and real-world implementation of artificial life robotic devices. Students and researchers will find this coverage of topics such as robotic energy autonomy, multi-locomotion of robots, biologically inspired autonomous robots, evolution in colonies of robotic insects, neuromorphic analog devices, self-configurable robots, and chemical and biological controllers for robots, will considerably enhance their understanding of the issues involved in the development of not-traditional hardware systems at the cusp of artificial life and robotics.